2012
DOI: 10.1002/jcc.22961
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of chemical reactions with COSMO‐RS: The extreme case of charge separation or recombination

Abstract: Many technically relevant chemical processes in the condensed phase involve as elementary reactive steps the formation of ions from neutral species or, as the opposite, recombination of ions. Such reactions that generate or annihilate charge defy the standard gas phase quantum chemical treatment, and also continuum solvation models are only partially able to account for the right amount of stabilization in solution. In this work, for such types of reaction, a solvation treatment involving the COSMO-RS method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 70 publications
2
35
0
Order By: Relevance
“…The COSMO‐RS approach, however, assumes a perfect mixture of the solvents instead of clusters surrounding the charges resulting in larger effects on ΔGsolT. Additional errors occur, because COSMO‐RS overestimates the hydrogen bonding donation capacity of chloroform . It is also known that the COSMO‐RS hydrogen bonding term has problems with secondary and tertiary aliphatic amines and polyether compounds (which are used as hosts here) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COSMO‐RS approach, however, assumes a perfect mixture of the solvents instead of clusters surrounding the charges resulting in larger effects on ΔGsolT. Additional errors occur, because COSMO‐RS overestimates the hydrogen bonding donation capacity of chloroform . It is also known that the COSMO‐RS hydrogen bonding term has problems with secondary and tertiary aliphatic amines and polyether compounds (which are used as hosts here) .…”
Section: Resultsmentioning
confidence: 99%
“…As in the gas phase, the calculated enthalpies and entropies in solution show poor agreement with experiment (see Supporting Information, Table S2), even with inclusion of the guest‐counterion‐separation. For charged systems, Deglmann and Schenk found deviations between experimental and calculated Gibbs energies ΔG of up to 23 kJ mol −1 , while experimental and calculated enthalpy or entropy term differ up to 112 or 86 kJ mol −1 , respectively. Besides the errors mentioned above, they suggest that the error arises from a wrong temperature dependence of enthalpy and entropy term in the hydrogen bonding term of COSMO‐RS, which would also apply to the systems investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the COSMO-RS model 56,57 has been tested for proton exchange and recombination reactions with reasonable accuracy. 58 Other promising approaches are the SMVLE 59 and CMIRS [60][61][62] methods. Essentially, these methods include a term to describe the effect of extremum electric field generated by charged solutes.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter case, solvation effects are in a similar energetic range as bond dissociations, or even larger. It has been shown that for such systems solvation models beyond continuum approaches are required and that COSMO‐RS represents a reasonable choice for a computation of thermodynamics (and kinetics) in aqueous and nonaqueous media . However, it should be noted that there are still cases where a straightforward application of this solvation protocol leads to inconsistencies, like in the prediction of aqueous p K a values where the general correlation between computed and experimental results is good but the slope of the correlation line systematically differs from one, which means that computed Gibbs free energies of dissociation suggest an overestimation of differences in acidity or basicity …”
Section: Methods Development and Benchmarkingmentioning
confidence: 99%